Transmission of Cognitive Bias and Fear From Parents to Children: An Experimental Study. Issue 5 (2nd September 2016) - Remmerswaal, Danielle; Muris, Peter; Huijding, Jorg
Abstract : This study explored the role of parents in the development of a cognitive bias and subsequent fear levels in children. In Experiment 1, nonclinical children ages 8–13 ( N  = 122) underwent a training during which they worked together with their mothers on an information search task. Mothers received instructions to induce either a positive or negative information search bias in their children. Experiment 2 investigated to what extent mothers own cognitive bias predicted children's information search bias. Mothers of 49 nonclinical children ages 9–12 received no explicit training instructions before working together with their child on an information search task. Experiment 1 demonstrated that mothers had a significant impact on children's cognitive bias and fear. More precisely, children who had received a negative parental training displayed an increase in negative information search bias and fear, whereas children who had received a positive parental training showed an increase in positive information search bias and a decrease in fear. In Experiment 2, it was found that children's information search biases after working together with their mothers were predicted by their mothers' initial cognitive bias scores. These findings can be taken as support for the intergenerational transmission of cognitive biases from mothers to children.